If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + 2(y + 1) = 7 Reorder the terms: -5 + 2(1 + y) = 7 -5 + (1 * 2 + y * 2) = 7 -5 + (2 + 2y) = 7 Combine like terms: -5 + 2 = -3 -3 + 2y = 7 Solving -3 + 2y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2y = 7 + 3 Combine like terms: -3 + 3 = 0 0 + 2y = 7 + 3 2y = 7 + 3 Combine like terms: 7 + 3 = 10 2y = 10 Divide each side by '2'. y = 5 Simplifying y = 5
| 5(4+2b)-3(1-4b)=-27 | | 5x-(2x+3)=5x-27 | | 6u-2u=-15 | | -[10x-(3x+2)]=-3-[4(3x-3)-3x] | | -2(3-5x)=4 | | 5x(2x+1)= | | -5(3p+2)-38=3(5p+4) | | 5+1.50=15.50 | | t^4+2t^2+1=0 | | 4.1x-2.6x-8=0.5 | | 3y+-5x=12 | | 2(x)+3(y)=120 | | 4x+-8=-6x+-2 | | 149=7y | | 2x*2+64+8x*2=8x*4 | | 10-8q=2(5-4q) | | 4a+7=5(a+5) | | -(1-3x)=11 | | 3(2+2x)=5(x-5) | | 2(3w-7)=w+11 | | 6(c-2)+9=3+c-6 | | 1.4-0.4x=5.2 | | 2*(7x+2)+12*(x+1)=12 | | 10-x=-13 | | X^2-x+17=0 | | X/2-(x-1/3)=1/9 | | -[10z-(14z+9)]=9+(3z+3) | | 6x-3=91 | | 40-3(2w+1)=11w-3(11+w) | | 3+x=117 | | x^3-2x^2+7x-14=0 | | 66/22r+(16/16-1)=r+(72/3/3) |